ERK signaling regulates light-induced gene expression via D-box enhancers in a differential, wavelength-dependent manner - Mracek, Philipp; Foulkes, Nicholas S. (PLOS ONE, 2013)
The day-night and seasonal cycles are dominated by regular changes in the intensity as well as spectral composition of sunlight. In aquatic environments the spectrum of sunlight is also strongly affected by the depth and quality of water. During evolution, organisms have adopted various key strategies in order to adapt to these changes, including the development of clocks and photoreceptor mechanisms. These mechanisms enable the detection and anticipation of regular changes in lighting conditions and thereby direct an appropriate physiological response. In teleosts, a growing body of evidence points to most cell types possessing complex photoreceptive systems. However, our understanding of precisely how these systems are regulated and in turn dictate changes in gene expression remains incomplete. In this manuscript we attempt to unravel this complexity by comparing the effects of two specific wavelengths of light upon signal transduction and gene expression regulatory mechanisms in zebrafish cells. We reveal a significant difference in the kinetics of light-induced gene expression upon blue and red light exposure. Importantly, both red and blue light-induced gene expression relies upon D-box enhancer promoter elements. Using pharmacological and genetic approaches we demonstrate that the ERK/MAPK pathway acts as a negative regulator of blue but not red light activated transcription. Thus, we reveal that D-box-driven gene expression is regulated via ERK/MAPK signaling in a strongly wavelength-dependent manner.